TRANSFORMASI DALAM PERFORMA PESAWAT TERBANG DI GENERASI BERBEDA - Diachirta Chrisna Ayu Dwi Harpini; Michael Febrianus Jhonny Saputra; Muhammad Daffa Ally (Bina Teknika, 2017)
Much people know that the fighter only just defense and security when wars in the air. Then, dont know that the fighters had many generation and each generation have a different. Because of that, we will tells to the reader that transformation of the fighter performance in different generation have advantages and disadvantages in the performances. With the comparation that we built, so we know which are the biggest performance.